Buddy system : understanding male friendships - Greif, Geoffrey L. (Oxford University Press, 2009)
Drawing on in-depth interviews with nearly 400 men, therapist and researcher Geoffrey L. Greif takes readers on a guided tour of male friendships, explaining what makes them work, why they are vital to the health of individuals and communities, and how to build the kinds of friendships that can lead to longer and happier lives.